The Relationship between Friendship and Social Life of Patients With Type 2 Diabetes with Depression - V. Kourkoumpas; K. Dimou; E. Dragioti; S. Mantzoukas; M. Gouva (European Psychiatry, 2022)
Introduction INTRODUCTION: Several studies have shown that the relationship between Diabetes and Depression is significant, but few have evaluated the relationship between this depression and patients’ social life.